The Effect of Cash Holdings, Free Cash Flow, and Profitability on Income Smoothing with Managerial Ownership as a Moderating Variable - Muhammad Satria; Fahrunil Annisa (GENTARA: management and accounting research, 2026)
Study This aim for analyze the influence of cash holding, free cash flow, and profitability against income smoothing, as well as test role ownership managerial as variables moderation in connection said. Object study is company sector mining companies listed on the Indonesia Stock Exchange during 2021–2025 period. Research data obtained through search report finance annual companies, including information regarding total assets, total debt, total income, as well as other relevant data with study. Population study consists of from 64 companies mining. Through purposive sampling technique, obtained 29 companies as sample study with period observation for five years, so that the total observation data used as many as 145 reports annual. Method analysis used in study This is multiple linear regression and Moderated Regression Analysis (MRA). Research result show that cash holding and free cash flow have an effect positive against income smoothing, whereas profitability influential negative against income smoothing. In addition, that, ownership managerial proven capable weaken the influence of cash holding and free cash flow on income smoothing. On the other hand, ownership managerial can also strengthen influence profitability against income smoothing